(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study investigates whether a floating structure can be characterized by replicating the waveinduced conditions within a small, homogeneous region. This is achieved by accelerating that region inside a tank. This study focuses on the motion response of a cylinder that is exposed -both numerically and experimentally- to vertical oscillations of the tank at a range of excitation frequencies encompassing its natural heave frequency, with the idea of capturing its frequency response. To gain insight into the system a numerical model in OpenFOAM was implemented, and an experimental campaign has been done. The numerical simulation modelled the core tank-floater interaction, excluding sloshing effects.